A homozygous missense variant in the MLC1 gene underlies megalencephalic leukoencephalopathy with subcortical cysts in large kindred: Heterozygous carriers show seizure and mild motor function deterioration. Issue 4 (17th December 2021) - Ain ul Batool, Syeda; Almatrafi, Ahmad; Fadhli, Fatima; Alluqmani, Majed; Sadia,; Ali, Ghazanfar; Basit, Sulman
Abstract: Megalencephalic leukoencephalopathy with subcortical cysts (MLC) is a rare type of leukodystrophy characterized by epileptic seizures, macrocephaly, and vacuolization of myelin and astrocyte. The magnetic resonance imaging of the brain of MLC patients shows diffuse white‐matter anomalies and the occurrence of subcortical cysts. MLC features have been observed in individuals having mutations in the MLC1 or HEPACAM genes. In this study, we recruited a six generation large kindred with five affected individuals manifesting clinical features of epileptic seizures, macrocephaly, ataxia, and spasticity. In order to identify the underlying genetic cause of the clinical features, we performed whole‐genome genotyping using Illumina microarray followed by detection of loss of heterozygosity (LOHs) regions. One affected individual was exome sequenced as well. Homozygosity mapping detected several LOH regions due to extensive consanguinity. An unbiased and hypothesis‐free exome data analysis identified a homozygous missense variant (NM_015166.3:c.278C>T) in the exon 4 of the MLC1 gene. The variant is present in the LOH region on chromosome 22q (50 Mb) and segregates perfectly with the disorder within the family in an autosomal recessive manner. The variant is present in a highly conserved first cytoplasmic domain of the MLC1 protein (NM_015166.3:p.(Ser93Leu)). Interestingly, heterozygous individuals show seizure and mild motor function deterioration. We propose that the heterozygous variant in MLC1 might disrupt the functional interaction of MLC1 with GlialCAM resulting in mild clinical features in carriers of the variant.